TrapREMI: A reaction microscope inside an electrostatic ion beam trap - Schotsch, Frans-Felix; Zebergs, I.; Augustin, S.; Lindenblatt, H.; Hoibl, Ludwig; Djendjur, D.; Schroeter, C. D.; Pfeifer, Thomas; Moshammer, R. (Review of scientific instruments, 2021)
A new experimental setup has been developed to investigate the reactions of molecular ions and charged clusters with a variety of projectile beams. An Electrostatic Ion Beam Trap (EIBT) stores fast ions at keV energies in an oscillatory motion. By crossing it with a projectile beam, e.g., an IR laser, molecular reactions can be induced. We implemented a Reaction Microscope (REMI) in the field-free region of the EIBT to perform coincidence spectroscopy on the resulting reaction products. In contrast to prior experiments, this unique combination of techniques allows us to measure the 3D momentum-vectors of ions, electrons, and neutrals as reaction products in coincidence. At the same time, the EIBT allows for advanced target preparation techniques, e.g., relaxation of hot molecules during storage times of up to seconds, autoresonance cooling, and recycling of target species, which are difficult to prepare. Otherwise, the TrapREMI setup can be connected to a variety of projectile sources, e.g., atomic gas jets, large-scale radiation facilities, and ultrashort laser pulses, which enable even time-resolved studies. Here, we describe the setup and a first photodissociation experiment on - H - + - 2 - H2+ - , which demonstrates the ion-neutral coincidence detection in the TrapREMI.